2020
DOI: 10.1002/esp.5000
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shoreline flooding enhances water turbidity by sediment resuspension: An example in a large Tibetan lake

Abstract: Rapid water level rise due to climate change has the potential to remobilize loose sediments along shorelines and increase the turbidity of nearshore waters, thereby impacting water quality and aquatic ecosystem health. Siling Lake is one of the largest and most rapidly expanding lakes on the Tibetan Plateau. Between 2000 and 2017, this lake experienced an increase in water level of about 8 m and a doubling in water turbidity. Here, using this lake as a study site, we used a wave model and high‐resolution remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Sediment transport along the YRD is mainly controlled by seasonal winds, because surface currents are weak (Wang et al, 2010). In shallow water environments, wave‐induced bed shear stress generally represents the primary mechanism for sediment resuspension (Fagherazzi & Priestas, 2010; La Forgia et al, 2019; Mi et al, 2020). Here, we calculated the bed shear stress using waves and water depth to further explore drivers of TSS variability.…”
Section: Study Area Data and Methodologymentioning
confidence: 99%
“…Sediment transport along the YRD is mainly controlled by seasonal winds, because surface currents are weak (Wang et al, 2010). In shallow water environments, wave‐induced bed shear stress generally represents the primary mechanism for sediment resuspension (Fagherazzi & Priestas, 2010; La Forgia et al, 2019; Mi et al, 2020). Here, we calculated the bed shear stress using waves and water depth to further explore drivers of TSS variability.…”
Section: Study Area Data and Methodologymentioning
confidence: 99%
“…Within lakes, the connections between water quantity F I G U R E 5 An inspection of the publications on satellite remote sensing of both water quantity and water quality between 1991 and 2021 (represented in Figure 4a) indicated that only 225 of the initially identified 486 publications distinctly assess both types of parameters. fluctuations and TSS are often explored through changes in water elevation causing redistribution and mobilization of sediment (e.g., Mi et al, 2020). Another area of interest for these studies is water temperature.…”
Section: Research Trends In Remote Sensing Of Inland Watermentioning
confidence: 99%
“…Of the publications, 18% ( N = 41) of studies mention TSS (Figure 5b), with over half of them relating specifically to river discharge or flow. Within lakes, the connections between water quantity fluctuations and TSS are often explored through changes in water elevation causing redistribution and mobilization of sediment (e.g., Mi et al, 2020). Another area of interest for these studies is water temperature.…”
Section: Research Trends In Remote Sensing Of Inland Watermentioning
confidence: 99%